2014
DOI: 10.1371/journal.pone.0102067
|View full text |Cite
|
Sign up to set email alerts
|

Tomato NAC Transcription Factor SlSRN1 Positively Regulates Defense Response against Biotic Stress but Negatively Regulates Abiotic Stress Response

Abstract: Biotic and abiotic stresses are major unfavorable factors that affect crop productivity worldwide. NAC proteins comprise a large family of transcription factors that play important roles in plant growth and development as well as in responses to biotic and abiotic stresses. In a virus-induced gene silencing-based screening to identify genes that are involved in defense response against Botrytis cinerea, we identified a tomato NAC gene SlSRN1 (Solanum lycopersicum Stress-related NAC1). SlSRN1 is a plasma membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 85 publications
3
54
0
Order By: Relevance
“…The significant accumulation of H 2 O 2 in leaves of the SlERF.A1 -, SlERF.A3 -, SlERF.B4 -, and SlERF.C3 -silenced plants after infection of B. cinerea ( Figure 7 ) may suggest that the function of SlERF.A1, SlERF.A3, SlERF.B4, and SlERF.C3 in defense response against B. cinerea links to ROS generation. Similar correlation of enhanced ROS accumulation and increased B. cinerea susceptibility were also observed in SlSRN1 -, SlMKK2 -, or SlMKK4 -silenced tomato plants (Li et al, 2014b; Liu et al, 2014b). …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The significant accumulation of H 2 O 2 in leaves of the SlERF.A1 -, SlERF.A3 -, SlERF.B4 -, and SlERF.C3 -silenced plants after infection of B. cinerea ( Figure 7 ) may suggest that the function of SlERF.A1, SlERF.A3, SlERF.B4, and SlERF.C3 in defense response against B. cinerea links to ROS generation. Similar correlation of enhanced ROS accumulation and increased B. cinerea susceptibility were also observed in SlSRN1 -, SlMKK2 -, or SlMKK4 -silenced tomato plants (Li et al, 2014b; Liu et al, 2014b). …”
Section: Discussionsupporting
confidence: 70%
“…It was shown that ABA regulates the immunity to B. cinerea in tomato through modulating the cuticle permeability and pectin composition in cell wall or suppressing the SA-mediated signaling pathway or the production of nitric oxide (Audenaert et al, 2002; Asselbergh et al, 2007; Curvers et al, 2010; Sivakumaran et al, 2016). A number of genes encoding receptor-like protein kinase TPK1b, transcriptional factors SHINE3, AIM1, SlDRW1, SlSRN1, SlSR1, and SlSR3L (Abuqamar et al, 2008, 2009; Buxdorf et al, 2014; Li et al, 2014a; Liu et al, 2014a,b), histone H2B monoubiquitination enzymes SlHUB1 and SlHUB2 (Zhang Y. et al, 2015), mitogen-activated protein kinase kinase SlMKK2 and SlMKK4 (Li et al, 2014b), phosphatidylinositol-phospholipase SlPLC2 (Gonorazky et al, 2016), NADPH oxidase SlRbohB (Li X. et al, 2015), 12-oxophytodienoate reductase SlOPR3 (Scalschi et al, 2015) and matrix metalloproteinase Sl3-MMP (Li D. et al, 2015) have been identified to play important roles in tomato immunity against B. cinerea . Enzymes involved in biosynthesis of vitamin B6 and trehalose-6-phosphate as well as concurrent over-activation of cytosolic glutamine synthetase and γ-aminobutyric acid shunt are also involved in tomato immune response to B. cinerea (Seifi et al, 2013; Zhang et al, 2014, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 467 differentially expressed genes, six were exclusively expressed in infected plants and only 1 in control plants (aldehyde dehydrogenase putative protein) (Table 5). NAC proteins are involved in developmental processes [59,60], hormone signaling [61,62], secondary cell-wall synthesis and programmed cell death [63,64] and in plant responses to abiotic and biotic stresses [6567]. The amino acid transporters are membrane proteins that mediate the flow of amino acids in plants and have various roles in the growth and development of plants, including metabolism of nucleotides, chlorophyll, hormones and secondary metabolites [68,69].…”
Section: Resultsmentioning
confidence: 99%
“…SISRN1 , a tomato NAC gene, was involved in the response to Botrytis cinerea (Liu et al 2014a). NTP1 and NTP2 , two NAC proteins from potato and N. benthamiana , are involved in the response to P. infestans (McLellan et al 2013).…”
Section: Discussionmentioning
confidence: 99%